Daya Hambat Ekstrak Biji Kopi Robusta (Coffea robusta) terhadap Pertumbuhan Fusobacterium nucleatum - Hakima, Anisa Nur; Ermawati, Tantin; Harmono, Happy (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2018)
Fusobacterium nucleatum is a bacteria found in normal flora of the oral cavity that plays a role in the occurrence of periodontal disease. The prevalence of periodontal disease in Indonesia reaches 70%. One treatment by using medicinal plants is robusta coffee beans. Robusta coffee beans contain volatile acids, chlorogenic acids, caffeine acids, phenols and caffeine suspected to be antibacterial. The objective of this study was to determine the inhibition of coffee robusta extract on growth of Fusobacterium nucleatum. This study used disc diffusion method with 4 samples in each study group. The study group consisted of 6 treatment groups (12,5%, 25%, 50% and 100% coffee robusta extract), positive control group (chlorhexidine gluconate 0,2%), and negative control group (sterile aquades). Data were analyzed using One Way Anova test and LSD (Least Significant Difference) test. Coffee robusta extract has the ability to inhibit the growth of Fusobacterium nucleatum. The concentration of coffe robusta extract 100%, 50%, 25%, 12,5% have same ability to inhibit the growth of Fusobacterium nucleatum.